Autotransplantation of the ovarian cortex after in-vitro activation for infertility treatment: a shortened procedure. Issue 8 (16th July 2021) - Zhang, Ling; Zhang, Jing; Zhai, Jun; Liu, Xiaochun; Deng, Weifen; Wang, Hong; Zhang, Zhiguo; Liu, Wei; Chen, Beili; Wu, Chongbo; Long, Huidong; Xu, Boqun; et al.
Abstract: STUDY QUESTION: Is it possible to establish a new in-vitro activation (IVA) protocol for infertility treatment? SUMMARY ANSWER: A new IVA procedure is an efficient and easily performed approach for infertility treatment of patients with diminished ovarian reserve (DOR). WHAT IS KNOWN ALREADY: IVA of primordial follicles with or without stimulators has been developed to treat patients with primary ovarian insufficiency (POI) successfully. However, the efficiency of the procedure is still very low. There is a requirement to optimize the protocol with increased efficiency for clinical application. STUDY DESIGN, SIZE, DURATION: Newborn mouse ovaries were used to establish a new 1-h IVA protocol with the mechanistic target of rapamycin (mTOR) stimulator phosphatidic acid (PA, 200 µM) and the phosphatidylinositol-3-kinase (PI3K) stimulator 740Y-P (250 µg/ml); a prospective observational cohort study in POI patients was performed on 15 POI patients and 3 poor ovarian response (POR) patients in three different centers of reproductive medicine in China. PARTICIPANTS/MATERIALS, SETTING, METHODS: One-third of ovarian cortex was removed and processed into bigger strips (1 × 1 cm 2, 1–2 mm thickness). Strips were then sutured back after treatment. The new approach only requires one laparoscopic surgery. MAIN RESULTS AND THE ROLE OF CHANCE: Follicular activation and development increased in cultured mouse and human ovarian tissues after 1 h of stimulator treatment. Compared with tiny ovarian cortex pieces (1 × 1 mm 2 ), large ovarian strips (1 × 1 cm 2 ) showed the lowest apoptotic signals after incubation. We applied the orthotropic transplantation procedure with large strips in the clinic, and 9 of 15 POI patients showed at least one-wave follicular growth during the monitoring period. One patient was reported with one healthy delivery after natural conception and another patient with a healthy singleton delivery after IVF. All the contacted patients (n = 13) responded with no side effects on their health 2–4 years after IVA procedure. LIMITATIONS, REASONS FOR CAUTION: Further clinical trials with a large number of well-defined patients are required to compare different IVA protocols. A long-term follow-up system should be set up to monitor patient's health in the future cohort study. WIDER IMPLICATIONS OF THE FINDINGS: By using stimulators, the findings in the study provide a more efficient IVA protocol for the treatment of patients with DOR. It requires only one laparoscopic surgery and thus minimizes patients' discomfort and costs. This strategy could be useful for patients diagnosed with POI and desire pregnancy as soon as possible after the operation. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Key Research and Development Program of China (2018YFC1003703 and 2018YFC1004203); the National Natural Science Foundation of China (81871221); Co-construction of Provincial Department (201601006). The authors have no conflict of interest to disclose. TRIAL REGISTRATION NUMBER: ChiCTR2000030872.